Shadow Education And Social Class Inequalities In Secondary Education In Greece: The Case Of Teaching English As A Foreign Language - Iakovos Tsiplakides (International Journal of Science and Society, 2023)
This article deals with the shadow education system of private tutoring which contributes to the reproduction of social class inequalities, focusing on the Greek public secondary education system. It presents a literature review of the issue and the findings of an empirical qualitative and quantitative research that aimed at examining the causes of the students’ massive resort to private supplementary tutoring for learning the English language, despite the fact that English is taught at school. The study also set out to examine the relationship between students’ socioeconomic background and resort to private supplementary tutoring and the relationship between socioeconomic background and knowledge of the English language as attested by official certifications. Research findings indicate that the widely spread resort to private supplementary tutoring has a negative impact on the teaching of English in Greek public lower secondary education. Using Bourdieu’s cultural reproduction theory, we argue that private supplementary tutoring makes closer the relationship between social class, familial cultural and economic capital and educational outcomes. Thus, upper and middle-class students are at an advantage, since they can move to the labour market with valued educational qualifications that enhance their occupational prospects. Finally, we discuss educational measures to address the problem.